2015
DOI: 10.1377/hlthaff.2015.0645
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity And Health Outcomes

Abstract: Almost fifty million people are food insecure in the United States, which makes food insecurity one of the nation's leading health and nutrition issues. We examine recent research evidence of the health consequences of food insecurity for children, nonsenior adults, and seniors in the United States. For context, we first provide an overview of how food insecurity is measured in the country, followed by a presentation of recent trends in the prevalence of food insecurity. Then we present a survey of selected re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
605
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,282 publications
(703 citation statements)
references
References 48 publications
13
605
2
2
Order By: Relevance
“…Some authors postulate that HFI is actually a risk factor for affective disorders, rather than the opposite (38,39) . Clearly, both directions are acceptable and further analyses examining non-recursive and/or time-related longitudinal transition models could shed further light on the matter (40,41) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors postulate that HFI is actually a risk factor for affective disorders, rather than the opposite (38,39) . Clearly, both directions are acceptable and further analyses examining non-recursive and/or time-related longitudinal transition models could shed further light on the matter (40,41) .…”
Section: Discussionmentioning
confidence: 99%
“…According to Gundersen and Ziliak (41) , a causal relationship between food insecurity and other health outcomes in cross-sectional studies is not as clear. In principle, this data collection strategy cannot ensure that IPV precedes HFI.…”
Section: Discussionmentioning
confidence: 99%
“…Food insecurity leads to many negative consequences for families. For example, 1 digitalcommons.unl.edu a literature review on the impact of food insecurity on health documents many negative short and long-term outcomes for children, adults, and also seniors (Gundersen and Ziliak 2015).…”
Section: Introductionmentioning
confidence: 99%
“…1 Studies from Canada and the United States have demonstrated that household food insecurity is a major public health problem, associated with elevated health care costs 2 and numerous adverse health outcomes. 3 The social epidemiology of food insecurity is well documented in Canada, with multiple characteristics indicative of financial vulnerability identified as risk factors, including low income [4][5][6][7] and renting versus owning a dwelling. [5][6][7][8] A recent multilevel analysis revealed a positive association between average rental cost in census metropolitan areas and food insecurity, 7 suggesting that the heightened vulnerability of renter households may be influenced by the cost of rents.…”
mentioning
confidence: 99%